Coupled thermo-hydro-mechanical modeling of fracture interactions in enhanced geothermal systems - Fabbri, Heber; Maedo, Michael A.; Cleto, Pedro [UNESP]; Manzoli, Osvaldo L. [UNESP]; Sánchez, Marcelo (Elsevier, 2025)
This paper presents the use of the mesh fragmentation technique (MFT) for modeling hydraulic stimulation and heat production in enhanced geothermal systems (EGS). This method simulates evolving hydraulic fractures induced by thermo-hydro-mechanical (THM) phenomena and their interaction with pre-existing natural fractures, forming an interconnected network for water circulation and energy production. The MFT combines high aspect ratio (HAR) elements within a standard finite element (FE), using appropriate constitutive models to describe mechanical, hydraulic, and thermal behaviors. Fracture evolution occurs naturally, governed only by local THM conditions and material properties, without needing special tracking algorithms or remeshing techniques. This approach relies on continuum mechanics and standard FE technology, employing simple models for energy dissipation, flow, and thermal transport due to enhanced porosity and permeability. Three application cases validate this technique. First, the proposed model shows excellent agreement with published thermo-hydraulic solutions, validating its implementation. Second, it effectively handles interactions between natural and hydraulic-driven fractures. Third, it models EGS operation for over 60 years under different in-situ stress scenarios and natural fracture densities. The results show the technique's effectiveness in modeling complex EGS scenarios and demonstrate its potential for optimizing EGS design.